Proceedings of the 27th ACM Conference on User Modeling, Adaptation and Personalization 2019
DOI: 10.1145/3320435.3320446
|View full text |Cite
|
Sign up to set email alerts
|

Combining Trending Scan Paths with Arousal to Model Visual Behaviour on the Web

Abstract: People with autism often exhibit different visual behaviours from neurotypical users. To explore how these differences are exhibited on the Web, we model visual behaviour by combining pupillary response, which is an unobtrusive measure of physiological arousal, with eye-tracking scan paths that indicate visual attention. We evaluated our approach with two populations: 19 neurotypical users and 19 users with autism. We observe differences in their visual behaviours as, in certain instances, individuals with aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, Balestra et al 62 showed that it can be used to study language impairments, text comprehension and production deficits. In addition, it can be used to identify fixation and saccades 63 , recognise affective states 64 and even reveal early biomarkers associated with ASD 65,66 . Furthermore, eye tracking can be used to detect saliency differences between ASD and TD children.…”
Section: Eye Gaze Datamentioning
confidence: 99%
“…For example, Balestra et al 62 showed that it can be used to study language impairments, text comprehension and production deficits. In addition, it can be used to identify fixation and saccades 63 , recognise affective states 64 and even reveal early biomarkers associated with ASD 65,66 . Furthermore, eye tracking can be used to detect saliency differences between ASD and TD children.…”
Section: Eye Gaze Datamentioning
confidence: 99%